Respuesta :
If you would like to simplify (6x^2 − 3 + 5x^3) − (4x^3 − 2x^2 − 16), you can calculate this using the following steps:
(6x^2 − 3 + 5x^3) − (4x^3 − 2x^2 − 16) = 6x^2 − 3 + 5x^3 − 4x^3 + 2x^2 + 16 = x^3 + 8x^2 + 13
The correct result would be x^3 + 8x^2 + 13.
(6x^2 − 3 + 5x^3) − (4x^3 − 2x^2 − 16) = 6x^2 − 3 + 5x^3 − 4x^3 + 2x^2 + 16 = x^3 + 8x^2 + 13
The correct result would be x^3 + 8x^2 + 13.
Answer:
Simplified form of [tex](6x^{2}-3+5x^{3})-(4x^{3}-2x^{2}-16)[/tex] is [tex]1x^{3}+8x^{2}+13[/tex] .
Step-by-step explanation:
As given the expression
[tex]= (6x^{2}-3+5x^{3})-(4x^{3}-2x^{2}-16)[/tex]
Now open the bracket
[tex]= 6x^{2}-3+5x^{3}-4x^{3}+2x^{2}+16[/tex]
[tex]= 1x^{3}+8x^{2}+13[/tex]
Therefore the simplified form of [tex](6x^{2}-3+5x^{3})-(4x^{3}-2x^{2}-16)[/tex] is [tex]1x^{3}+8x^{2}+13[/tex] .